Agricultural development: Policies for sustainable irrigation management - Ahmad, Ahfandi; Tarman, Risma Niswati (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2024)
The rate of environmental degradation in Indonesia, which is increasing from time to time, is one of the phenomena. One of the implications of forest destruction is the decreasing availability of water to meet the community's needs in the dry season, including irrigation water for agricultural purposes. The purpose of this research is to formulate the determinants of policy strategies in sustainable irrigation management; create and synthesize various basic assumptions that support policy strategies in sustainable irrigation management; develop the structure of policy strategies in sustainable irrigation management through the synthesis of environmental, economic, technical and institutional aspects. This research uses a system modeling approach through the Soft System Methodology (SSM) method, which is oriented towards preparing guidelines for action (action-oriented). Sustainable Irrigation Management has three sub-models: water resources conservation, irrigation network management/rehabilitation, and irrigated agriculture development. Developing sustainable irrigation management policies requires awareness, commitment, and alignment of local governments with active community participation. Prioritization of activities to realize sustainable irrigation management is compiled through FGDs using the Exponential Comparison Method, which provides a focus of action on the operation, maintenance, and rehabilitation of irrigation networks and immediately issued regional regulations related to the empowerment of irrigation institutions and Irrigation Commissions.